KUALITAS PELAYANAN PUBLIK PADA PERUSAHAAN DAERAH AIR MINUM (PDAM) STUDI KASUS DI KABUPATEN REMBANG - Indrastuti Dwi Suryani; Purwoko .; Susilo Utomo (Journal of Politic and Government Studies, 2015)
PDAM Rembang (Rembang’s government water supply company) is the Regional Owned Company which was established to provide drinking water to the people of rembang with the quality and quantity in accordance with the standard set. As a regional company, PDAM Rembang often showed so many obstacles and problems in the past years. According BPPSPAM in 2010, PDAM Rembang was classified in healthy performance, otherwise it also included one of six of government water supply companies in Central Java which filed for bankruptcies due to lack of income. In the implementation of operational activities of public services in PDAM Rembang, it can be indicated that service quality is still low in terms of the distribution of clean water and the continuity of water to all customers.The purpose of this study is to find out what the dimension of tangible, reliability, responsibility, assurance, and empathy by Zeithaml (1990) is determining of public services quality at the Regional Water Supply Company (PDAM) Rembang . This study used quantitative research methods supported by tools of observation, questionnaires, and documents. The total of research samples were taken from 265 respondents which were drawn from 18.619 customers by using Table Cohen Manion and Morrison with some considerations, that an approximate population of 10.000, a 90 % the confidence level of the research, and an alpha of 0.1. Sampling technique used proportional stratified random sample (stratified proportional Random Sample). Then, the analysis of the data used Customer Satisfied Index (CSI) to determine the level of customer satisfaction.The results showed that the dimension of tangible, reliability, responsibility, assurance, and empathy by Zeithaml (1990) is determining of public services quality at the Regional Water Supply Company (PDAM) Rembang. From the calculation of the conformity level of the service attributes could be seen that the average level of concordance between performance and expectations of each service dimension, showed that tangible dimension has a suitability level of 89.09% indicating very satisfied, reliability dimension has a suitability level of 80.04% indicating satisfied, responsiveness dimension has a suitability level of 86.09% indicating satisfied, assurance dimension has a suitability level of 85.64% indicating satisfied, and empathy dimension has a suitability level of 86.12% indicating satisfied.Keywords: Public Service Quality, The Regional Water Supply Company (PDAM)